EFEK MODEL PEMBELAJARAN INQUIRY TRAINING TERHADAP KETERAMPILAN PROSES SAINS PADA PEMBELAJARAN FISIKA - Dalimunthe, Jumlia Syaulani Rizki; Bukit, Nurdin (JURNAL IKATAN ALUMNI FISIKA, 2017)
This study aims to determine the effect of science process skills the applies to the inquiry training learning model, conventional learning, and to the differences in skills the process of science students. The research is a quasi experimental and the sample using the method of a cluster random sampling. The result showed the average value of the pretest experimental class 37,5 with the standard deviation 6,93 and the average value of the control class 36,8 with the standard deviation 7,10. In both classes of the test data obtained pretest that the ability of the students at the beginning of the second class of the same. After the treatment is given experimental class with inquiry training learning model and control class with conventional learning model the data obtained with the postest average yield experimental class and control class was 74,83 and 69,07. In both classes of the test data obtained posttes that both classes of data are normally distibuted and homogeneous along with there is the difference at a result of effect the training inquiry learning model to the science proses skills in learning physics.